2020
DOI: 10.1101/2020.09.13.20189530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low lymphocyte count is a risk factor for Parkinson’s disease

Abstract: Importance: Biomarkers for the early detection of Parkinsons disease (PD) are needed; emerging evidence implicates immune dysregulation. Altered leukocyte differentials and C-reactive protein (CRP), common markers of immune function, occur in patients with PD. Whether these changes drive pathogenesis remains unclear. Objectives: We sought to identify whether peripheral immune dysregulation can be seen as a pre-diagnostic feature of PD, and whether it appears to play a causal role. Design: We examined the relat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 54 publications
(79 reference statements)
0
4
1
Order By: Relevance
“…Differences between our study and the studies by Yazdani et al and Jensen et al [14,15] which reported a lower lymphocyte count to be associated with an increased risk of incident PD could be explained by several factors. First, these two previous studies [14,15] used hospital discharge international classification of diseases (ICD) codes or self-reported PD to define incident events. Both studies reported a significant delay of multiple years between the first symptom onset and the date of incident PD recorded in the study [14,15,49].…”
Section: Sensitivity Analysiscontrasting
confidence: 99%
See 4 more Smart Citations
“…Differences between our study and the studies by Yazdani et al and Jensen et al [14,15] which reported a lower lymphocyte count to be associated with an increased risk of incident PD could be explained by several factors. First, these two previous studies [14,15] used hospital discharge international classification of diseases (ICD) codes or self-reported PD to define incident events. Both studies reported a significant delay of multiple years between the first symptom onset and the date of incident PD recorded in the study [14,15,49].…”
Section: Sensitivity Analysiscontrasting
confidence: 99%
“…In addition to the effect of lymphocytes, we found that participants with a higher GLR, PLR, and adapted SII [19,42] monocytes and the risk of PD [14,15]. Because of these conflicting previous findings and the wide confidence intervals around our estimates, the association between monocyte count and PD warrants further investigation.…”
Section: Sensitivity Analysismentioning
confidence: 58%
See 3 more Smart Citations